The Impact of TBXA2R Gene Variants on the Risk of Aspirin-Induced Upper Gastrointestinal Bleeding: A Case-Control Study - Forgerini, Marcela [UNESP]; Gini, Ana Luísa Rodriguez [UNESP]; Lemos, Isabele Held [UNESP]; Santos, Ana Caroline Silva [UNESP]; Bessa, Maria Paula [UNESP]; Valentini, Sandro Roberto [UNESP]; Mastroianni, Patrícia de Carvalho [UNESP] (SAGE Publications, 2024)
Objective: Upper gastrointestinal bleeding (UGIB) has been identified as a potential adverse drug reaction associated with the use of low-dose aspirin (LDA). This study aimed to investigate the relationship between variants in the TBXA2R gene, which is involved in platelet aggregation, and the risk of UGIB in patients with cardiovascular diseases treated with LDA. Methods: A case-control study was conducted at a Brazilian hospital complex. Three groups were defined: (1) case group (n = 50): patients with cardiovascular disease who used LDA and were diagnosed with UGIB of non-variceal etiology, (2) LDA control group (n = 50): patients with cardiovascular disease who used LDA without developing UGIB, and (3) healthy control group (n = 189). Data were collected through face-to-face interviews, and blood samples were collected for the analysis of Helicobacter pylori infection and genotyping of 3 genetic variants [rs2238631 (C > T), rs4807491 (A > G), and rs1131882 (A > G)]. Results: The case group had a significantly higher frequency of carriers of the rs4807491.G allele compared to the control group of LDA users (P-value =.004). No significant difference was observed in the proportion of carriers of the rs2238631.T and 1131882.G variants between the studied groups. Carriers of rs2238631.T (OR: 4.515, 95% CI: 1.37-14.89) and rs4807491.G allele (OR: 3.232, 95% CI: 1.12-9.37) exhibited a higher risk of UGIB. Conclusion: These findings suggest that the presence of the rs2238631 and rs4807491 variant alleles is associates with a 3- to 4-fold increased risk of UGIB in patients with cardiovascular diseases treated with LDA. Future studies with larger sample sizes should confirm these results and to better identify individuals who may benefit from chronic LDA use.
Keywords: G-protein-coupled receptors; gastrointestinal hemorrhage; pharmacogenetics; single nucleotide polymorphism; thromboxane A2 receptors